A Solvent‐free energetic coordination polymer [N, N‐(3, 4‐dinitropyrazolate)Ag]: synthesis, structure and energetic performance. Issue 16 (20th June 2022) - Zhang, Xiaopeng; Wu, Yige; Wang, Pengcheng; Lin, Qiuhan; Chen, Shusen; Jin, Shaohua; Xu, Yuangang; Lu, Ming
Abstract: A novel solvent‐free energetic coordination polymer [Ag(3, 4‐dnp)] was performed by dehydration. The structure was confirmed by single‐crystal X‐ray crystallography and the Ag(I) ions are coordinated in bidentate‐bridging mode. The results of thermal analysis (thermogravimetric and accelerating rate calorimeter) show that this compound has higher thermal stability than that of the traditional CHON‐containing energetic materials, RDX, HMX and CL‐20. The detonation velocity and detonation pressure of [Ag(3, 4‐dnp)] are 5.532 km s −1, 15.88 GPa, respectively, which is lower than that HMX, RDX and TNT, and comparable with the 2D MOFs [Ag(Mtta)] based on the Ag ions and 5‐methyl tetrazole. The impact and friction sensitivities of this compound are infinitely close to RDX, state‐of‐the‐art explosive. The coordination polymers based on metal ions and nitropyrazole are promising potential as energetic materials. Abstract :